2008
DOI: 10.1002/ajmg.b.30813
|View full text |Cite
|
Sign up to set email alerts
|

The TGM2 gene is associated with schizophrenia in a British population

Abstract: Several lines of evidence have suggested an interesting link between gluten ingestion and schizophrenia. Increased levels of gliadin antibodies have been observed in patients with schizophrenia. Tissue transglutaminase (transglutaminase 2, TGM2) is involved in the production of gliadin antibodies. To investigate genetic association of the TGM2 gene with schizophrenia, we detected eight single nucleotide polymorphisms (SNPs) present in the gene among 131 family trios composed of fathers, mothers and affected of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…TGM2 has been shown to be important for several different cellular processes such as cytoskeleton stabilization, apoptosis, cell differentiation, cell adhesion, and even GTP-hydrolysing activity. TGM2 activity is also well known to be involved in celiac disease (CD), a chronic, auto-immune mediated, small-intestinal disorder characterized by inflammatory injury to the mucosa following ingestion of wheat gluten [40]. TGM2-specific antibodies are almost exclusively found in CD and are therefore used as a diagnostic indicator of CD [41].…”
Section: Discussionmentioning
confidence: 99%
“…TGM2 has been shown to be important for several different cellular processes such as cytoskeleton stabilization, apoptosis, cell differentiation, cell adhesion, and even GTP-hydrolysing activity. TGM2 activity is also well known to be involved in celiac disease (CD), a chronic, auto-immune mediated, small-intestinal disorder characterized by inflammatory injury to the mucosa following ingestion of wheat gluten [40]. TGM2-specific antibodies are almost exclusively found in CD and are therefore used as a diagnostic indicator of CD [41].…”
Section: Discussionmentioning
confidence: 99%
“…Four single nucleotide polymorphisms (SNPs) present in the TGM2 gene were selected for genotyping, including rs2076380, rs7270785, rs4811528, and rs6023526, as these four SNPs were reported to be associated with schizophrenia in our previous study (Bradford et al, 2009). These four SNPs were genotyped by PCR-based restriction fragment length polymorphism analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the expression of the TGM2 gene was upregulated in the anterior cingulate cortex of patients with schizophrenia (patent number: WO/2004/053157). Genetic analysis showed a strong association of the TGM2 gene with schizophrenia in a British population (Bradford et al, 2009), although a genome-wide association (GWA) study has failed to show an association signal at the TGM2 locus (Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014). It is worth noting that the P-value of 5 × 10 -8 set in the GWA study of schizophrenia may inflate the type II errors.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no direct evidence that these mutations contribute to the development of diabetes in these patients. In a British population eight non-coding SNPs across the TGM2 gene were genotyped and it was suggested that the detected variants were associated with schizophrenia and TGM2 may have a role in the development of this mental disease (Bradford et al 2009). In another study a major fraction of human protein coding genes was examined in breast and colorectal cancer (Sjöblom et al 2006) to determine the spectrum and extent of somatic mutations; TGM2 was one of the genes with a somatic mutation (Gly660Val).…”
Section: Snps In the Tgm2 Genementioning
confidence: 99%